Contemporary Developments and Perspectives in International Health Security (IntechOpen, 2023)
The COVID-19 pandemic has transformed healthcare systems worldwide. Even as the world transitions out of the pandemic, numerous health threats remain, the biggest of which is climate change. This book examines both the virus and climate change in the context of international health security. It begins with chapters on the effect of COVID-19 on pregnancy and the perinatal period and its relationship to toxic stress. Subsequent chapters address climate change and its effects on human health and wellbeing, natural disaster frequency and severity, and occupational accidents.